2018
DOI: 10.1007/s10964-018-0822-9
|View full text |Cite
|
Sign up to set email alerts
|

The Rise and Fall of Depressive Symptoms and Academic Stress in Two Samples of University Students

Abstract: Self-reported depressive experiences are common among university students. However, most studies assessing depression in university students are cross-sectional, limiting our understanding of when in the academic year risk for depression is greatest and when interventions may be most needed. We examined within-person change in depressive symptoms from September to April. Study 1 (N = 198; 57% female; 72% white; Mage = 18.4): Depressive symptoms rose from September, peaked in December, and fell across the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 39 publications
7
63
0
7
Order By: Relevance
“…However, it is also possible that students in the training group may have continued to practice skills learned—thus leading to more significant gains over time. The impact on perceived stress was evident at both post‐training and semester‐end, which is important given its predictive relationship to longitudinal outcomes (Barker et al, ; Zahniser & Conley, ). In comparison to prior studies (Conley et al, ), the current intervention more robustly impacted depression rather than anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also possible that students in the training group may have continued to practice skills learned—thus leading to more significant gains over time. The impact on perceived stress was evident at both post‐training and semester‐end, which is important given its predictive relationship to longitudinal outcomes (Barker et al, ; Zahniser & Conley, ). In comparison to prior studies (Conley et al, ), the current intervention more robustly impacted depression rather than anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The skills targeted overlap significantly with cognitive behavioral therapies (CBT) for anxiety and depression, with the additional target of growth mindset processes highlighted in psychological resilience research (Steinhardt & Dolbier, 2008). Anxiety and depression represented primary symptom outcomes, with a secondary outcome of perceived stress, as a transdiagnostic contributor to student mental health (Barker, Howard, Villemaire-Krajden, & Galambos, 2018;Zahniser & Conley, 2018). We also aimed to identify potential mechanisms of change to inform future intervention optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, at this point of time this sample is larger than in most other epidemiological studies investigating students' health (Barker et al, 2018;Ngin et al, 2018). Nevertheless, it would be beneficial to replicate the study in more universities in each country.…”
Section: Strengths and Limitationsmentioning
confidence: 94%
“…Overall, we observed that students with food insecurity are disproportionately launching their university careers with poorer mental health in addition to socioeconomic disadvantage. In our prior work, 38% to 50% of first-year students scored at or above clinical screening thresholds for depression 12 and risk for depression was greater for students with current financial stress 13 .…”
Section: Discussionmentioning
confidence: 80%